Research on stimulating mechanism and restricting factors of employees’ innovative behaviour under COVID-19 - Wu, Guosong (Frontiers in Environmental Science, 2022)
Innovation is the foundation of an enterprise’s survival and development. Employee innovation is the source of enterprise innovation. Under the COVID-19 epidemic, staff innovation is crucial to whether an enterprise can transform a crisis into an opportunity. However, the negative emotions caused by the epidemic will hinder staff innovation. The influence of the COVID-19 pandemic in China was investigated from May 2020 to October 2021 by using questionnaires.This study explores the motivating mechanism and restricting factors of employees’ innovative behaviour under sudden public crisis events. The software SPSS 22.0 is used for the descriptive statistical and correlation analyses of the collected data. Enterprise managers need to study the influencing factors of employees’ innovative behaviour under the COVID-19 epidemic to solve the problem of employees’ negative emotions. Based on the statistical analysis of 639 valid questionnaires for employees of high-tech enterprises, this study explores the motivating mechanism and influencing factors of employees’ innovative behaviour from the aspects of positive psychological quality and leaders’ interpersonal emotion management. This study also uses work autonomy as a mediating variable to verify its mediating role in the process of employees’ positive psychological quality and leaders’ interpersonal emotion management on innovation behaviour. This study tested the moderating effect of employees’ perceived corporate social responsibility on the relationship between employees’ positive psychological quality, leaders’ interpersonal emotion management and innovative behaviour. Through the statistical analysis of 639 valid questionnaires of employees in high-tech enterprises, the relevant model assumptions are verified.Therefore, under the COVID-19 pandemic, enterprises should take responsibility from the aspect of caring for employees to promote the positive effect of employees’ psychological attitudes on work results. This study provides countermeasures to ensure the smooth progress of employee innovation activities.